(untitled) (Contemporary Mathematics, 2024)
In this paper, we convert certain dual q-integral equations involving third Jackson q-Bessel functions to the first and second kind Fredholm q-integral equations by extending the multiplying-factor method introduced by Nobel. We also apply these results to convert a certain triple q-integral equations to two simultaneous Fredholm q-integral equations